Les garanties contractuelles dans les transactions internationales comportant la fourniture de biens ou de services - Hannani, Mahomed (Les Cahiers de droit, 1985)
It is common knowledge that liberalizing international exchanges does not eliminate the risks involved in international trade. For indeed, parties to an international commercial transaction are often far distant from one another and naturally know little about their respective financial or industrial situations as well as the laws and customs in force in these countries. It is these circumstances that brought about various advance payment schemes such as the letters of credit. Yet world expansion of commerce that is largely due to hydro-electric projects and other projects linked together on a worldwide basis has given rise to contract guarantees. In this article the author deals with guarantees which mainly concern tender bond, performance bond, instalment reimbursement bond. By means of these guarantees, an importer may demand that a third party whose solvency is recognized will guarantee the economic bond of the exporter. The demand for supplying a contract guarantee may also be required by the international body that finances an economic project or by way of legislation in some countries. After having described the machinery of these guarantees, the author examines the legal nature and validity of them. He then analyses the legal relationship of parties to this institution. He concludes by considering different cases that may prevent the realisation of the guarantee.